Merjenje napovednikov blagostanja med mladostniki v Sloveniji - Kozina, Ana (Psihološka obzorja (Ljubljana), 2019)
Well-being has gained importance in psychological research as well as in the field of education. However, there is a lack of validated questionnaires in Slovenia that would measure well-being in different domains in childhood and youth. In the present paper we focused on psychometric properties of two children and adolescent well-being measures: Middle Years Development Instrument (MDI; Schonert-Reichl et al., 2013) and Measure of Adolescent Well-Being (EPOCH; Kern, Benson, Steinberg, & Steinberg, 2016). In order to validate the questionnaires, their structure, reliability and convergent and discriminant validity were analysed. Analyses were conducted on PISA 2015 subsample for Slovenia in an additional well-being study, with sample size 3224 (age: M = 16.65; SD = 4.19 years). Confirmatory factor analyses (CFA) were conducted separately for MDI and two dimensions of EPOCH. CFA indicated adequate fit for all expected models. Results showed satisfactory internal reliability of all subscales (alpha coefficients ranged from 0.72 to 0.92). Our research demonstrates evidence for convergent and discriminant validity (correlations between subscales, correlations with PYD questionnaire and with gender). The validation of presented measures speaks in favour of use of these questionnaires for studying factors of well-being in Slovenia.
Keywords: adolescents; blagostanje; Measure of Adolescent Well-Being EPOCH; measurement; Mera napovednikov blagostanja mladostnikov EPOCH; merjenje; Merjenje razvoja otrok MDI; merske značilnosti; metric characteristics; Middle Years Development Inventory MDI; mladostniki; positive psychology; Positive Youth Development PYD; pozitivna psihologija; test validity; veljavnost; Vprašalnik spodbujanja pozitivnega razvoja mladih PYD; well being